Relation between the meteorological and hydrological sequence in the subcuenca Chancos, Ancash - Macedo García, Henri Salvador (2022)
Drought monitoring, including its severity, spacing and duration, becomes an essential tool to establish a drought risk management and mitigation plan. This paper aims to compare the Standardized Precipitation Index (SPI) with the Standardized Streamflow Index (SSI) in the Chancos sub-basin, Ancash. The statistical evaluation will be done through the analysis of homogeneity and trends of the data set, then for the analysis of the statistical association is included the Pearson correlation coefficient (PCC), root mean square error (RMSE), relative bias (BIAS) and the Nash-Sutcliffe coefficient (NSE) to determine the degree of consistency between the drought indices. The study revealed that the characteristics of meteorological and hydrological drought in the study period show similarity of patterns which is indicated by the good correlation coefficient between them. In addition, the best comparative analysis was of SSI3 with SPI3 and the least was of SSI12 with SPI12 obtaining a Pearson correlation of 0.82 and 0.41 respectively. In general, SPI and SSI show a good performance for the estimation of meteorological and hydrological drought characteristics at monthly level.